How do you solve (2x+8)(3x-6)=0 using any method?

1 Answer
May 4, 2017

x=-4 or x=2

Explanation:

Expand the equation from the brackets

(2x+8)(3x-6)=0
(color(red)(2x)+8)(color(red)(3x)-6) Multiply the highest power of x first
(color(red)(2x)+8)(3xcolor(red)(-6)) Next multiply by the next highest power

(2xcolor(blue)(+8)(color(blue)(3x)-6) Multiply by the highest power
(2xcolor(blue)(+8)(3xcolor(blue)(-6)) Multiply by next highest power.

Therefore,
6x^2-12x+24x-48=0
6x^2+12x-48=0 ------------------Divide the equation by 6
x^2+2x-8=0 --------------------------Simplify the equation
(x+4)(x-2)=0
x+4=0 or x-2=0
x=-4 or x=2